Perbandingan Pembuatan dan Implementasi Kebijakan Indonesia dalam Menghadapi Status Darurat Narkotika dengan Filipina dan Portugal [The Making and Implementation of Indonesia's Policy in Facing the Narcotics Emergency Status in Comparison with the Philippines and Portugal] - Qanszelir GB Pandjaitan XIV; Selly Stefany Novelina (Universitas Pelita Harapan, 2022)
Indonesia is one of the countries that have to deal with narcotics problems. Even since the first period of President Joko Widodo's administration in 2014, Indonesia is often in the narcotics emergency status, where President Joko Widodo and other government officials have consistantly mentioning that status on numerous occassions. However, the making and the implementation of the narcotics-related policies in Indonesia have not reflecting any kind of seriousness in facing that aforementioned status. This is resulting in the number of any forms of narcotics-related crime that have not showed any signs of significant decline yet. In addition, people are often shocked with the kinds of people who became the actors of the narcotics-related crimes in Indonesia. Not only the civil society, but the government officials, celebrities, even the law enforcement officials are also the actors of the narcotics-related crime. This research is using the case study and comparative method by looking at the Philippines and Portugal who are also facing the similar status with Indonesia. The result of this research shows that Indonesia, either the government or the civil society, still have a lot of homeworks in dealing with the narcotics emergency status in comparison with the Philippines and Portugal who are facing the similar narcotics emergency status with Indonesia.Bahasa Indonesia Abstract: Indonesia adalah salah satu negara yang selalu harus berurusan dengan permasalahan narkotika. Bahkan, sejak memasuki periode pertama Presiden Joko Widodo pada 2014, Indonesia sering disebut berada dalam status darurat narkotika, di mana Presiden Joko Widodo dan para pemangku jabatan pemerintahan lainnya juga sering menyampaikan status tersebut di berbagai kesempatan. Namun, pembuatan dan implementasi kebijakan di Indonesia yang berkaitan dengan narkotika belum bisa mencerminkan adanya keseriusan dalam menghadapi status darurat narkotika tersebut. Hal ini berujung kepada angka kejahatan narkotika dalam berbagai bentuk belum menunjukkan adanya tanda-tanda mengalami penurunan yang berarti. Bahkan, variasi pelaku kejahatan narkotika di Indonesia cukup membuat banyak orang terheran-heran. Tidak hanya rakyat biasa, tetapi juga para pemangku jabatan, selebritas, bahkan aparat penegak hukum juga tidak luput sebagai pelaku kejahatan narkotika. Penelitian ini menggunakan metode studi kasus dan komparatif dengan melihat Filipina dan Portugal yang kurang lebih berada dalam status darurat narkotika yang mirip dengan Indonesia. Hasil dari penelitian ini menunjukkan bahwa Indonesia, baik pemerintah dan masyarakat, masih memiliki pekerjaan rumah yang besar dalam menghadapi status darurat narkotika jika dilihat dari perbandingan dengan Filipina dan Portugal yang menghadapi status darurat narkotika yang serupa.